2022
DOI: 10.3390/biology11101445
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Expression Analysis of Mollusk-like Growth Factor: A Secreted Protein Involved in Pacific Abalone Embryonic and Larval Development

Abstract: Growth factors are mostly secreted proteins that play key roles in an organism’s biophysical processes through binding to specific receptors on the cell surface. The mollusk-like growth factor (MLGF) is a novel cell signaling protein in the adenosine deaminase-related growth factor (ADGF) subfamily. In this study, the MLGF gene was cloned and characterized from the digestive gland tissue of Pacific abalone and designated as Hdh-MLGF. The transcribed full-length sequence of Hdh-MLGF was 1829 bp long with a 1566… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Therefore, it is plausible that Hdh-HGAP may have direct or indirect involvement in these developmental events. In fact, previous studies have reported the involvement of secreted growth-related genes in the metamorphosis of Pacific abalone [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is plausible that Hdh-HGAP may have direct or indirect involvement in these developmental events. In fact, previous studies have reported the involvement of secreted growth-related genes in the metamorphosis of Pacific abalone [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three-year-old reproductively mature 12 females’ and 4 male’s abalone were induced for artificial fertilization. After spawning, unfertilized eggs (UFE) and sperm were collected, and artificial fertilization was performed following the procedure described by Hanif et al [ 22 ]. After fertilization, samples of target stages, including fertilized eggs (FE), 2-cell (2-CL) and 4-cell (4-CL) stages, morula (MOR), trochophore (TRP) larvae, veliger (VLG) larvae, and juveniles (JUV), were collected through microscopic observation.…”
Section: Methodsmentioning
confidence: 99%
“…Artificial fertilization of Pacific abalones was performed following the procedure described by Hanif et al [29]. Briefly, male abalones with fully mature gonad were induced to release sperm by sunlight exposure (60 min shell-side down and 40 min shell-side down).…”
Section: Fertilization and Sample Collection From The Embryonic And L...mentioning
confidence: 99%
“…The expression levels of Hdh-TPM were observed in the different organs of adult Pacific abalone and the various embryonic and larval developmental stages of Pacific abalone. All qRT-PCRs were conducted following the protocol previously described by Hanif et al [29]. In qRT-PCR analysis, three biological replicates were used in this study.…”
Section: Quantitative Real-time Pcr (Qrt-pcr) Analysismentioning
confidence: 99%
“…As mollusks, Haliotis discus hannai is one of the most important economic species in shellfish culture in China. It is an urgent and arduous task to explore the mechanism of larval development and put forward the management measures which can guide production practice [ 11 ]. It is clear that the Hippo pathway plays an important role in the larval development of mollusks, but there has been little report so far.…”
Section: Introductionmentioning
confidence: 99%